Futures of the African Buffalo - (:unkn) unknown (My University, 2023)
In this chapter we envision the possible futures of the African buffalo populations in Africa by reflecting on the regional and international factors and their relationships that could positively or negatively impact the healthiness of the buffalo species in the next 30 years. Using the expertise of the authors of this book, we drafted and validated a list of factors of change that could impact the futures of African buffalo populations on the continent and use a set of prospective methods, i.e. structural analysis, critical uncertainty matrix and morphological analysis to develop seven synopses which provided caricatural African contexts within which the consequences for African buffalo populations could be imagined. In 2050, the futures of the African buffalo will vary according to each country specific social, technical, economic, environmental, political and value contexts. In a context of climate change that will impact increasingly the environmental contexts in Africa, good futures for buffalo were often associated with political stability and good governance. The proportion of African living in cities will also be important. The ratio of urban versus rural African will not only determine the intensity of the agricultural pressure on land but also the African worldviews towards nature and its conservation. The influence of non-African states will also be determinant, especially in extractive industries and their request for land. A pivotal factor is the conservation models that will prevail in 2050: to what extent they are still influenced and constrained by part of the Western opinion; to what extent they are funded by them; and to what extent African worldviews push for the design of new conservation models based on different relationship between people and nature. Probably, landscapes associating land-sparing (e.g. national parks) and land-sharing management options, based on the sustainable use of natural resources will provide the best futur
Keywords: African Research